Fine particulate matter in acute exacerbation of COPD - Ni, Lei; Chuang, Chia-Chen; Zuo, Li (Frontiers in Physiology, 2015)
Chronic obstructive pulmonary disease (COPD) is a common airway disorder. In particular, acute exacerbations of COPD (AECOPD) can significantly reduce pulmonary function. The majority of AECOPD episodes are attributed to infections, although environmental stress also plays a role. Increasing urbanization and associated air pollution, especially in developing countries, have been shown to contribute to COPD pathogenesis. Elevated levels of particulate matter (PM) in polluted air are strongly correlated with the onset and development of various respiratory diseases. In this review, we have conducted an extensive literature search of recent studies of the role of PM2.5 (fine PM) in AECOPD. PM2.5 leads to AECOPD via inflammation, oxidative stress, immune dysfunction, and altered airway epithelial structure and microbiome. Reducing PM2.5 levels is a viable approach to lower AECOPD incidence, attenuate COPD progression and decrease the associated healthcare burden.